PEMANTAUAN DAN PEMBERDAYAAN KADER LANSIA TENTANG ASAM URAT DENGAN MEDIA BODESERA DI WILAYAH KERJA PUSKESMAS MULYOREJO SURABAYA JAWA TIMUR - Lailatun Ni’mah; Ika Nur Pratiwi; Abu Bakar; Laily Hidayati (Jurnal Layanan Masyarakat (Journal of Public Services), 2020)
Gout are nitrogen compounds that result from the process of catabolism (breakdown) of purine from both diet and endogenous nucleic acid (deoxyribonuleic acid DNA). Most of the members of the Posyandu Lansia in the working area of the Mulyorejo Health Center are gout sufferers. These community service activities include: 1) monitored uric acid levels of members of the Posyandu Lansia 2) health education for elderly members and cadres about gout: definition, symptom signs, and gout diet with Bodesera media (Booklets and Models of Uric Acid-Free Healthy Foods) 3) training on how to use gout test kits for elderly cadres and 4) administering gout tests to elderly cadres. The results of the pre-test showed that elderly gout sufferers, and elderly cadres had diverse knowledge about the definition of gout, diet of gout, signs of gout and how to check gout. These results are still at less value, while the results of the post-test assessment indicate that the participants' knowledge has increased. This community service activity is needed to improve understanding of gout in the working area of the Mulyorejo Health Center Surabaya. Community service activities can be carried out regularly so that the health of elderly Posyandu members can be monitored and elderly cadres are able to independently check the acid levels of the elderly.Abstrak Asam urat, gout, pirai atau arthritis pirai adalah senyawa nitrogen yang dihasilkan dari proses katabolisme (pemecahan) purin baik dari diet maupun dari asam nukleat endogen (same deoksiribonuleat DNA). Sebagian besar anggota Posyandu Lansia wilayah kerja Puskesmas Mulyorejo adalah penderita asam urat. Kegiatan pengabdian masyarakat ini meliputi: 1) memantau kadar asam urat para anggota Posyandu Lansia 2) pendidikan kesehatan kepada anggota dan kader Lansia tentang asam urat: definisi, tanda gejala, dan diet asam urat dengan media Bodesera (Booklet dan Model Makanan Sehat Bebas Asam Urat) 3) pelatihan cara menggunakan alat tes asam urat kepada kader lansia serta 4) pemberian alat tes asam urat kepada kader lansia. Hasil pretest menunjukkan para lansia penderita asam urat, dan mempunyai pengetahuan yang beragam mengenai definisi asam urat, diet asam urat, tanda asam urat dan cara pemeriksaan asam urat. Hasil tersebut masih berada pada nilai kurang, hasil penilaian posttest menunjukkan bahwa pengetahuan para peserta mengalami peningkatan. Kegiatan pengabdian masyarakat ini diperlukan untuk meningkatkan pemahaman tentang asam urat di wilayah kerja Puskesmas Mulyorejo Surabaya. Kegiatan pengabdian masyarakat dapat dilaksanakan secara teratur agar kesehatan lansia anggota Posyandu lansia dapat terpantau dan kader Lansia mampu mengecek kadar asam lansia dengan mandiri.Gout are nitrogen compounds that result from the process of catabolism (breakdown) of purinefrom both diet and endogenous nucleic acid (deoxyribonuleic acid DNA). Most of the membersof the Posyandu Lansia in the working area of the Mulyorejo Health Center are gout sufferers.These community service activities include: 1) monitored uric acid levels of members of thePosyandu Lansia 2) health education for elderly members and cadres about gout: definition,symptom signs, and gout diet with Bodesera media (Booklets and Models of Uric Acid-FreeHealthy Foods) 3) training on how to use gout test kits for elderly cadres and 4) administeringgout tests to elderly cadres. The results of the pre-test showed that elderly gout sufferers, andelderly cadres had diverse knowledge about the definition of gout, diet of gout, signs of goutand how to check gout. These results are still at less value, while the results of the post-testassessment indicate that the participants' knowledge has increased. This community serviceactivity is needed to improve understanding of gout in the working area of the MulyorejoHealth Center Surabaya. Community service activities can be carried out regularly so that thehealth of elderly Posyandu members can be monitored and elderly cadres are able toindependently check the acid levels of the elderly.